Cinderella [videorecording (DVD)] - Cabello, Camila, 1997-; Menzel, Idina; Driver, Minnie; Galitzine, Nicholas; Porter, Billy; Brosnan, Pierce; Baillio, Maddie, 1996-; Spencer, Charlotte (Sony Pictures Home Entertainment, 2022)
A modern movie musical with a bold take on the classic fairy tale. Our ambitious heroine has big dreams and with the help of her fab Godmother, she perseveres to make them come true.